Linguistic capital, phonological dissonance, and international student adaptation: An analytic autoethnography - Munyanyi, Albert (Journal of International Students, 2026)
Movement between intra-English contexts can produce significant cognitive and psychological disruption. Research on international student adaptation has extensively examined language proficiency, sociocultural adjustment, and academic integration, yet an underexplored dimension is phonological transition across national varieties of English even among formally fluent speakers. This analytic autoethnography examines the transition from a British English–based educational background to American doctoral study, tracing the cognitive, affective, and identity-related consequences of phonological dissonance. The study conceptualizes phonological adaptation as a matter of epistemic access and symbolic legitimacy. Seven themes emerged: illusion of fluency, phonological shock, listening fatigue, participation hesitation, micro-interactional confidence erosion, accent negotiation, and time as adaptation capital. Findings position phonological decoding as structural to academic integration and offer implications for pre-arrival preparation, institutional practice, and faculty awareness.